DNA Barcode of Red Junglefowl Gallus gallus L, 1958 (Aves: Phasianidae) of Sumatra Based on Mitochondrial COI DNA Gene - Jarulis Jarulis; Nurmeiliasari Nurmeiliasari; Hery Haryanto; Iqwati Vilanda (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Genetic data of red junglefowl (Gallus gallus) from southern Sumatra is valuable for conservation efforts in Indonesia. A mitochondrial COI DNA gene sequencing was performed to elucidate its genetic character, single nucleotide polymorphism, genetic distance, and phylogeny. Blood samples (±0.5 ml) from 20 individuals of Gallus gallus were taken from the living collections of the people of Bengkulu Province (Central Bengkulu Regency and Seluma Regency) and South Sumatra Province (North Musi Rawas Regency) from May to November 2021. Total DNA isolation followed the procedure of The Spin-Column Protocol Kit uses the Dneasy® Blood and Tissue Kit, Qiagen. DNA replication using the Polymerase Chain Reaction technique with primers (COIGG_F and COIGG_R) using MEGA 10.0 software and Bioedit for data analysis. The results revealed716 conserved sites, 16 variable sites, 9 parsimony sites, and 6 singleton sites from the 732 bp nucleotide sequence. Six specific sites (SNPs) as barcodes for Sumatran Junglefowl were found at sequences 51, 273, 327, 721, 729, and 732. The mean genetic distance between individuals was 0.1%, between populations was 0.8%, between species was 7.4%, and between genera was 15.5%. The red junglefowlof South Sumatra Province and Bengkulu Province are closely related with 98% bootstrapping and separated from other Gallus in the same group (ingroup) with 100% bootstrap. The Gallus-gallus group is quite far apart from the outgroup species in the Phasianidae family with 47-100% bootstrap. Red junglefowl from southern Sumatra has genetic differences from other chickens in the world and these differences can be used as a species barcode and as origin identification the widely traded red jungle fowl.